GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI SD N JARAKAN KABUPATEN BANTULTAHUN AJARAN 2016/2017 - Dyah Hediana Windasari (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2017)
The purpuso of research is to determine : (1) The style of principal leadership in improving the  professional  competence  of  any  that  have  been  formed  on  the  teachers;  (2)  the  professional competence of any that have been formed on the teacher; (3) the principal obstacles and ways to improve  the  professional  competence  of  teachers. This  study  a  descriptivestudy  with  qualitative apporoach.  Data  collection  techniques  using  observation,  interviews,  and  documentation.  Data analysis technique performed with data collection, data reduction, presenting data, and conclusions. The  results  showed  that  (1)  the  principal’s  leadership  style  used  improving  the  professional competence  of  teachers  is  the  style  of  executive  leadership,  development,  democratic,  organizer and administrator; (2) professional competence that has been formed by the teacher is capable of mastering the subject matter in accordance with the field of study that teaches, is able to apply the methodology and learning strategies, capable of designing and utilizing various media and learning resources, is able to carry out the evalution of learning, capable of develop programs of learning, and able to carry out elements of support; (3) barriers experienced principals are the facilities, the age  factor  and  bustle  head  teacher  of  the  school.  How  did  the  head  of  the  school  in  improving the professional competence of teachers is to give more credence to the teachers and training of teachers, PLPG, PPG, and teacher certification.